An Inadvertent Concurrent Replication: Same Roadmap, Different Journey. (July 2016) - Lemons, Christopher J.; King, Seth A.; Davidson, Kimberly A.; Berryessa, Teresa L.; Gajjar, Shimul A.; Sacks, Lia H.
Replication is a critical aspect of scientific inquiry that presents a variety of challenges to researchers, even under the best of conditions. We conducted a review of replication rates in special education journals similar to the review conducted by Makel et al. in this issue. Unknowingly conducting independent reviews allowed for an unexpected opportunity to examine how two teams of researchers attempted to replicate a previously published study and explore similarities and differences between the outcomes. In our review, we identified 70 replication studies published between 1997 and 2013, indicating that 0.41% of published articles in special education journals are replication studies. Similar to findings reported by Makel et al., our review indicates that most replications are successful and that successful replications are more likely when author overlap occurs. Although there are similar patterns in the two data sets, an examination of exact agreement on article inclusion revealed an agreement rate of 15.2%. Possible explanations for the discrepancy and implications for future directions are provided.